The Role Of Teachers In Early Childhood Mathematics Play - Oktariani; Nurani, Yuliani; Utami, Ade Dwi (Exploration in Early Childhood Research, 2024)
The practice of early childhood education contains various content, one of which is mathematics content, in its application to early childhood the teacher plays a big role in developing this content to make it a fun mathematics activity, but based on field results found in one of the kindergartens in Maja subdistrict it shows that teachers do not know properly the appropriate mathematical content for children so that in practice teachers more often only introduce the concept of numbers and counting. Based on the problems found, the aim of this research is to examine and analyze the role of teachers in introducing mathematical content through mathematical play activities. Researchers use literature studies to review the role of teachers in introducing early childhood mathematics content through mathematical play activities. So, to describe the results of this research, the analysis qualitative descriptive method is the most appropriate method to use, so that we get results that show that the role of teachers in introducing mathematical content to children can be the fulcrum of children's understanding of mathematics, in the sense of good teacher ability in content and ability. teachers in developing mathematics content into mathematical play activities become the basis for creating meaningful and enjoyable mathematics play classes, so that mathematics play activities become a means of providing a deep understanding of mathematics to children in a fun way.